Studies on the Production of Gasoline from Heavy oil (furnace oil) by Thermal Cracking - Jamal, MS; Ismail, Mohammad; Miah, M Yunnus; Haque, M Naimul; Banik, Sujit Kumar (Bangladesh Journal of Scientific and Industrial Research, 2010)
Heavy fuel oil (furnace oil) was thermally cracked by thermal cracker under different parametric conditions such as cracking temperature, molar ratio of heavy oil to diesel and cracking time to optimize the yield of the final product. In this thermal cracking process, the yield was gradually increased with the increase in temperature and time. After a certain temperature and time no significant increase in yield was observed. Thermo gravimetric analysis (TGA) was done to observe the percentage of weight loss with increasing temperature. The obtained cracked oil was fractionated by atmospheric vacuum distillation unit. Products obtained from different experiments under different conditions showed almost similar physico-chemical properties. Optimization was done on the basis of yield (%wt). The optimum yield (56.2%) of light petroleum fraction (gasoline) was obtained under the following experimental conditions: cracking temperature: 445°C; molar ratio of furnace oil to diesel 95:05; and cracking time: 30 min. The properties such as density, water content, ash content, pour point, flash point, viscosity, range of boiling point, sulphur content, carbon residue, octane number etc. of the obtained light petroleum fraction were found almost similar to that of the commercial grade gasoline. Key words: Furnace oil; Thermal cracking; Gasoline; Thermo gravimetric analysis. DOI: 10.3329/bjsir.v44i4.4601 Bangladesh J. Sci. Ind. Res. 44(4), 473-478, 2009